VD_FINDINFO HC / 2015 / 255 vom 3. März 2015 - VD Tribunal cantonal (2015)
RETRAITVOIE DE DROIT, DÉPENS | 106 al. 1 CPC (CH), 107 al. 1 let. c CPC (CH), 107 al. 1 let. f CPC (CH), 110 CPC (CH), 122 CPC (CH), 319 let. b ch. 1 CPC (CH)